2010
DOI: 10.1088/0957-4484/21/11/115207
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-confined direct band transitions in tensile strained Ge/SiGe quantum wells on silicon substrates

Abstract: We directly demonstrate quantum-confined direct band transitions in the tensile strained Ge/SiGe multiple quantum wells grown on silicon substrates by room temperature photoluminescence. The tensile strained Ge/SiGe multiple quantum wells with various thicknesses of Ge well layers are grown on silicon substrates with a low temperature Ge buffer layer by ultrahigh vacuum chemical vapor deposition. The strain status, crystallographic, and surface morphology are systematically characterized by high-resolution tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…Using B 1.0 for high Ge mole fractions as in Ref. [19], the Ge mole fraction of the top interface of GOI2 is 0.86. Note that this intensity ratio method only gives information on an averaged composition over the penetration depth of the 514-nm excitation source.…”
mentioning
confidence: 99%
“…Using B 1.0 for high Ge mole fractions as in Ref. [19], the Ge mole fraction of the top interface of GOI2 is 0.86. Note that this intensity ratio method only gives information on an averaged composition over the penetration depth of the 514-nm excitation source.…”
mentioning
confidence: 99%
“…Tensile-strained Ge QWs have demonstrated direct-gap transitions. 8,9 In this work, electroluminescence from strained 10 period n-Ge multiple quantum well (MQW) LEDs grown directly on a silicon wafer is presented which produces electroluminescence at the important 1.55 lm wavelength at room temperature (298 K).…”
mentioning
confidence: 99%
“…In 2011, Ren et al [44] experimentally demonstrated that Ge/Si 0.15 Ge 0.85 MQWs on a Si 0.1 Ge 0.9 relaxed buffer can provide optical modulation from light wavelengths of 1450–1550 nm with an applied electric field of as high as 20 V μ m −1 . Additionally, application of tensile strain can be used to obtain Ge QWs with direct gap transition around 1.55 μ m. Chen et al [45] and Carroll et al [46] prepared tensile-strained Ge/SiGe MQWs through tensile-strained Ge virtual substrate, and showed direct-gap excitonic transition around 1.55 μ m from the photoluminescence and transmission spectra at room temperature. To our knowledge, no QCSE has yet been demonstrated from such an approach.…”
Section: Electro-absorption In Ge-rich Sige Materials Systemsmentioning
confidence: 99%